Edukasi Dhuafa Mart Dalam Pengembangan Ekonomi Syariah Lokal Di Air Tiris - Winario, Mohd; Reza, Saru; Priyatno, Arif Mudi; Putri, Elen Sri Ega (Journal of Community Sustainability, 2025)
This community service activity aims to improve public understanding of sharia economics through education conducted at Dhuafa Mart, Air Tiris. Dhuafa Mart is a sharia-based economic business that not only functions as a trading center, but also as a means of empowering the poor community. Through this education program, the community is given an understanding of the concept of halal transactions, Islamic financial management, and sharia-based business strategies that can be applied in micro and small businesses. The methods used in this activity are stages of socialization, training, and mentoring for managers and local business actors. Data and evaluation of the success of the program are carried out through observation, interviews, and questionnaires to education participants. The results of the activity show that the education provided has a positive impact on increasing public understanding of the principles of sharia economics and its application in daily businesses. In addition, this program also encourages active community participation in developing sustainable sharia-based businesses. As a recommendation, there needs to be strengthening of synergy between Dhuafa Mart and sharia financial institutions and local governments to provide further support in developing sharia-based businesses.